PM.58 Clinical Outcomes in Pregnant Women Newly Reclassified as Gestational Diabetes (GDM) Using IADPSG Criteria. (26th April 2013) - Anthony, R; Ikomi, A; Khan, R; Angala, P; Kiss, S
Abstract : Background: There are widespread concerns about the potential resource implications of implementing the International Association of the Diabetes and Pregnancy Study Group (IADPSG) criteria for diagnosing GDM. However, another important consideration is the risks facing undiagnosed cases if the new criteria are not adopted. In our unit, since 2006 we have offered a 3 point OGTT [fasting, 1 & 2 hours]. Hence our projected increase in number of GDM cases is solely related to the lower IADPSG fasting threshold [5.1] and not it's addition of a 1 hr threshold. Aims: To identify women with 75 g OGTT fasting levels between IADSPG and WHO thresholds [5.1–5.9], and normal 1–2 hour levels. To ascertain the extent of diabetes related outcomes in these undiagnosed cases. Materials and Methods: Retrospective study of OGTT results for all women who delivered in our unit between 1 st January 2009 and 31 st December 2011. Outcome data for 129 selected cases was obtained from our Protos Maternity information system. Results: All deliveries ended in live births but the fetal macrosomia rate (>4 kg) was 30% [39/129]. Using a cut off of 4.5 kg the macrosomia rate was 5.4%. The caesarean section rate for macrosomic babies was 23% [9/39]. Neonatal hypoglycaemia was diagnosed in 6.2% [4/129] of the babies and 3.1% [4/129] needed immediate admission to NICU. However, none of the admissions to NICU were directly related to neonatal hypoglycaemia. Conclusions: The significant incidence of fetal macrosomia in this cohort of women suggests untreated diabetes and potential benefits in adopting IADSPG criteria.